A Simplified Finite Element Approach for Modeling of Multilayer Plates - Taiyou Liu; Xinbo Ma; Pak Kin Wong; Jing Zhao; Zhengchao Xie; V. A. Melo Cristino (Shock and Vibration)
The multilayer plate has a great potential for automotive and aerospace applications. However, the complexity in structure and calculation of the response impede the practical applications of multilayer plates. To solve this problem, this work proposes a new plate finite element and a simplified finite element (FE) model for multilayer plates. The proposed new plate finite element consists of the shear and extension strains in all layers. The multilayer structure with the proposed new plate finite element is regarded as a reference to calculate the reference value of the transverse response. The simplified FE model of multilayer plates is proposed based on the equivalent bending stiffness by curve fitting of the reference value of the transverse response. Numerical study shows that this approach can be used to set up the simplified FE model of multilayer plates.